History, current status and future prospets of geoelectromagnetic research in Ukraine - Burakhovich Т.; Kushnir А. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The current state and prospects for the development of geoelectromagnetic methods are considered. Problems and ways to solve them, new ideas and new tasks are discussed. Modern experimental methods of observations, universal software complexes for their processing, methods of three-dimensional model building of various geological and tectonic units of Ukraine are analyzed. The geological and geophysical interpretation results of regional and local three-dimensional models are shown. Geoelectrical inhomogeneities in the earth’s crust and upper mantle of Ukraine, which are characterized by abnormally low and abnormally high values of resistivity, have been revealed. Zones of high conductivity that reach the surface are defined by subvertical heterogeneity and form a galvanically connected system. It spatially correlates with deep faults of various ranks, identified by geological data. The nature of conductivity anomalies at the depth of up to 2.5 km is due to the presence of conductive mineral associations (sulfides, graphite) in the zones of metasomatic processing rocks that lead to the formation of ore mineralization (uranium, gold, rare metals). In the earth’s crust at the depths of 5–30 km and the upper mantle of 50–120 km, most likely, traces of the influence of modern mantle fluids are reflected. More and more often, according to the latest data, the nature of anomalies is considered as the result of the joint activity of electronic and ionic conductivity. Conductivity anomalies of the earth’s crust and upper mantle indicate possible zones of geodynamic activation, and deep faults are defined by zones of increased permeability through which mantle fluids are unloaded through the lithosphere. In particular, the connection of conductivity anomalies on the territory of Ukraine with the processes of petroleum and ore deposit formation is demonstrated.